2013
DOI: 10.3126/kumj.v10i3.8014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Arterial Oxygen Saturation and Hematocrit, and Effect of Slow Deep Breathing on Oxygen Saturation in Himalayan High Altitude Populations

Abstract: Background The oxygen saturation of haemoglobin is reduced in high altitude-living organisms. Increase in the hematocrit is responsible for rise in the hemoglobin concentration so that the oxygen carrying capacity in the hypobaric hypoxic subject is elevated. Objectives To compare two different high altitude populations, in order to study the relationship between arterial oxygen saturation and hematocrit. Methods lIn the cross-sectional study of two populations residing at altitude of 2800 m and 3760 m are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…The results of the present study showed an increase in the red blood cell count of rats under high-altitude hypoxic conditions; therefore, it was speculated that the increased red blood cell count could cause hyperuricemia. Moreover, a high red blood cell count could cause an increase in blood viscosity [ 46 ], which can suppress blood flow and inhibit circulation, resulting in myocardial damage [ 47 , 48 ]. Platelets are released by mature megakaryocytes in the bone marrow, and changes in platelets are mainly due to an imbalance in their production and destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed an increase in the red blood cell count of rats under high-altitude hypoxic conditions; therefore, it was speculated that the increased red blood cell count could cause hyperuricemia. Moreover, a high red blood cell count could cause an increase in blood viscosity [ 46 ], which can suppress blood flow and inhibit circulation, resulting in myocardial damage [ 47 , 48 ]. Platelets are released by mature megakaryocytes in the bone marrow, and changes in platelets are mainly due to an imbalance in their production and destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Ahora bien, los valores encontrados en la SpO 2 pueden estar relacionados con la respuesta hiperventilatoria mencionada inicialmente, Aunque con respecto a la saturación arterial de oxígeno y su relación con el hematocrito, estudios como el de Nepal et al, encontraron que el aumento en la concentración de glóbulos rojos produce mayor saturación en individuos residentes en altura, observando además que una respiración lenta y profunda mejora la saturación tanto en altura como a nivel del mar 32 , Teniendo en cuenta que en este estudio la exposición a la altura es aguda, el papel fundamental para la adaptación a la hipoxia se otorga a las bombas hemodinámicas y neumodinámicas las cuales permiten el transporte de oxígeno a los diferentes tejidos, mientras que en exposiciones crónicas el trabajo de estas bombas se reduce gracias al aumento de Hb, CaO2, obteniendo una función celular del 100% efectiva en individuos bien adaptados a la altura 33 .…”
Section: Discussionunclassified
“…Selain itu, latihan ini juga dapat mencegah terjadinya atrofi pada otot, meningkatkan volume otot, stabilitas sendi dan mengurangi edema. Sedangkan pernapasan yang dilakukan secara dalam danperlahan pada saat latihan slow deep breathing akan memperbaiki saturasi oksigen didalam tubuh (Nepal et al, 2013). Peningkatan jumlah oksigen didalam tubuh akan menstimulasi munculnya iksidasi nitrin, oksidasi nitrin akan masuk kedalam otak dan paru-paru yang akan membuat tubuh menjadi lebih tenang, oksidasi nitrin juga akan mempengaruhi pembuluh darah menjadi lebih elastis sehingga menyebabkan terjadinya vasodilatasi pada pembuluh darah sehingga tekanan darah menjadi turun (Tarwoto., 2011 [18]).…”
Section: Pembahasanunclassified